2017
DOI: 10.1055/s-0037-1603315
|View full text |Cite
|
Sign up to set email alerts
|

Assistance to Normal Delivery in Two Public Maternities: Perception of the Health Professionals

Abstract: Purpose To evaluate the perception of health professionals involved in the labor process and the assistance to normal delivery, comparing two hospitals in the city of Goiânia, Brazil, regarding the perception of these professionals when they are performing the routines and practices recommended by the World Health Organization (WHO). Methods This is an analytical comparative study with a quantitative approach, performed in two public hospitals in the city of Goiânia, in the state of Goiás, Brazil. The study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…The acceleration of labor with amniotomy and/or oxytocin, plays an important role in the "cascade of interventions" and the reduction rate on spontaneous delivery. 16 Data from a study conducted in the State of Goiás, 17 containing a sample of 43 deliveries, described amniotomy at 16.3% of the deliveries, similar to that found in this study (15.2% and 17.2%), and the administration of oxytocin at 32.6%, higher than the values found at the maternity in query (26.5% and 14.6%), which monitors its use in the first and second periods of delivery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acceleration of labor with amniotomy and/or oxytocin, plays an important role in the "cascade of interventions" and the reduction rate on spontaneous delivery. 16 Data from a study conducted in the State of Goiás, 17 containing a sample of 43 deliveries, described amniotomy at 16.3% of the deliveries, similar to that found in this study (15.2% and 17.2%), and the administration of oxytocin at 32.6%, higher than the values found at the maternity in query (26.5% and 14.6%), which monitors its use in the first and second periods of delivery.…”
Section: Resultsmentioning
confidence: 99%
“…This fact emphasizes the importance of moni-toring the indicators on practices and non-recommended interventions, once, if they appear in the WHO guidelines it is because there are indications of their performance, confirmed by national and regional research spheres. 1,[8][9][10][11][15][16][17][18] This study allowed to comprehend the indicators on childbirth care present at the service and by analyzing them based on the WHO recommendations. It is expected to contribute to the services and professionals to understand the importance of registering the indicators and assessing childbirth care and their possible progress in the aspects that are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Non-pharmacological methods of pain relief can be used alone or together with the multidisciplinary team (physiotherapists, nurses, nursing technicians, doctors, and doulas), depending on the parturient’s choice and the hospital’s infrastructure [ 3 6 ]. Some studies have demonstrated the effectiveness of walking and massage in reducing pain and increasing pain tolerance during labor [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%